2004
DOI: 10.1080/10284150412331279827
|View full text |Cite
|
Sign up to set email alerts
|

A Low Protein Diet Causes an Increase in the Basal Levels and Variability of Mean Arterial Pressure and Heart Rate in Fisher Rats

Abstract: The correlation between nutrition and cardiovascular related disorders is a well-established fact. Previous work from our Laboratory has suggested a significant compromise of cardiovascular reflexes in conscious rats submitted to a low-protein (LP) diet. Our working hypothesis is that the basal level of mean arterial pressure (MAP), variability of the mean arterial pressure (VMAP), heart rate (HR) and variability of heart rate (VHR) are altered in rats submitted to a protein restricted diet. Two experimental g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 15 publications
(17 reference statements)
4
43
0
1
Order By: Relevance
“…Also, there may be diff erences related to these two experimental models. Studies suggest that malnutrition during discrete periods of life (e.g., gestation, lactation, during weaning and after weaning) can produce diff erent levels of homeostasis imbalance; nevertheless, there is a consensus that protein deprivation in any period of life can lead to cardiovascular and metabolic imbalances (Barker, 2007;Cohen, 2004;El et al, 1999;Gallo, 1981;Oliveira et al, 2004;Roseboom et al, 1999). Unfortunately, there are few studies addressing post-weaning protein malnutrition and most of them are from our group.…”
Section: As Depicted Inmentioning
confidence: 70%
See 1 more Smart Citation
“…Also, there may be diff erences related to these two experimental models. Studies suggest that malnutrition during discrete periods of life (e.g., gestation, lactation, during weaning and after weaning) can produce diff erent levels of homeostasis imbalance; nevertheless, there is a consensus that protein deprivation in any period of life can lead to cardiovascular and metabolic imbalances (Barker, 2007;Cohen, 2004;El et al, 1999;Gallo, 1981;Oliveira et al, 2004;Roseboom et al, 1999). Unfortunately, there are few studies addressing post-weaning protein malnutrition and most of them are from our group.…”
Section: As Depicted Inmentioning
confidence: 70%
“…Previous studies from our lab have shown that afterweaning malnutrition affects neural mechanisms involved in cardiovascular homeostasis (Bezerra et al, 2011a;Bezerra et al, 2011b;Loss et al, 2007;Martins et al, 2011;Oliveira et al, 2004;Penitente et al, 2007;Tropia et al, 2001). While the exact mechanism remains to be understood, there is evidence indicating that malnutrition can aff ect the release of neurotransmitters and receptor affi nity in several areas of the central nervous system (El et al, 1999;Gotoh et al, 1996;Seidler et al, 1990) The rostral ventrolateral medulla (RVLM) is a bulbar site among the neural pathways of cardiovascular refl exes (e.g., barorefl ex); it contains reticulo-spinal neurons that innervate the pre-ganglionic sympathetic neurons (Ross et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It also affects cardiovascular and immunology system due to endothelial dysfunction, hypertension and anemia syndrome or disturb growth and development of thymus and spleen [3,17,25]. Protect role against protein deficiency in cardiovascular and immune system can play vitamin B 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Fisher's rats fed a low protein diet had an elevated mean arterial pressure, mean arterial pressure variability, heart rate, and heart rate variability compared to control rats on a normal diet. 24 Tozawa et al reported that blood pressure variability was a poor prognostic risk factor for cardiovascular disease in patients with end-stage renal failure. 25 Twenty-four-hour blood pressure variability is an independent risk factor for cardiovascular mortality 26 and is associated with end organ damage.…”
Section: Discussionmentioning
confidence: 99%